Parturient on Magnesium Infusion and Its Effectiveness as an Adjuvant Analgesic after Cesarean Delivery: A Retrospective Analysis - Tanmay H. Shah; Abby R. Rubenstein; Edward S. Kosik; Stephen W. Heimbach; Abhinava S. Madamangalam (The Scientific World Journal)
Background. Perioperative use of intravenous magnesium as part of multimodal analgesia has been increasing in recent years in an effort to decrease the use of opioids. The aim of this study was to evaluate the effectiveness of magnesium sulfate infusion in lowering analgesic requirement and decreasing the intensity of pain score after cesarean delivery. Methods. Sixty-four patients who underwent cesarean delivery under spinal anesthesia were included in this medical record review: 32 patients received magnesium infusion after cesarean delivery for treatment of mild preeclampsia (Mg group); 32 patients received routine post-cesarean delivery care (control group). Primary outcome was total analgesic consumption and secondary was visual analogue scores (VAS) of pain in each group during the first 24 hours following delivery. These measures were compared using Student’s t-tests and Mann-Whitney U-tests. Results. Our study found that patients in the Mg group had significantly less requirement for analgesia than the control group. In the 24 h after cesarean delivery, the Mg group received significantly less intravenous ketorolac (the standard initial rescue analgesic agent) when compared to the control group (79 ± 23 mg vs. 90 ± 0 mg; P = 0.008). The Mg group also received significantly less intravenous morphine equivalents than the control group (median 5.0 (IRQ: 0.0 – 10.0) vs. 9.3 (IRQ: 6.0 – 21.1); P = 0.001) during the first 24 h after cesarean delivery. The Mg group also had significantly lower VAS pain scores than the control group (median 1.75 (IRQ: 0.4 – 2.6) vs. median 3.2 (IRQ: 2.3 – 4.5); P < 0.001). Conclusions. Our results suggest that magnesium sulfate infusion decreases total analgesic requirements and lowers VAS pain scores during the first 24 h after cesarean delivery.